2010
DOI: 10.1021/ic902231b
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Rare-Earth Iron Arsenides RE12Fe57.5As41 (RE = La, Ce)

Abstract: The rare-earth iron arsenides RE(12)Fe(57.5)As(41) (RE = La, Ce) have been prepared by direct reactions of the elements in the presence of a Sn flux. Analysis of single-crystal X-ray diffraction data reveals that they adopt a new orthorhombic structure type (Pearson symbol oP236, space group Pmmn, Z = 2; a = 10.8881(9) A, b = 25.753(2) A, c = 12.5436(10) A for RE = La; a = 10.8376(8) A, b = 25.639(2) A, c = 12.4701(9) A for RE = Ce). In this metal-rich arsenide, the complex three-dimensional network (derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Combinations of distinct chemical bonding not only provide conditions for realization of varying crystal structures but can also engender notable structural complexity. The interplay of chemical composition and peculiar bonding frequently gives rise to interesting properties in TM pnictides. Some of these compounds have been proposed as potential thermoelectric materials, because of their appropriate electronic properties, coupled with low thermal conductivity, e.g., Yb 14 MnSb 11 or A TM 4 Pn 12 , where A is an alkali, alkaline-earth, or rare-earth metal .…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of distinct chemical bonding not only provide conditions for realization of varying crystal structures but can also engender notable structural complexity. The interplay of chemical composition and peculiar bonding frequently gives rise to interesting properties in TM pnictides. Some of these compounds have been proposed as potential thermoelectric materials, because of their appropriate electronic properties, coupled with low thermal conductivity, e.g., Yb 14 MnSb 11 or A TM 4 Pn 12 , where A is an alkali, alkaline-earth, or rare-earth metal .…”
Section: Introductionmentioning
confidence: 99%
“…An undetermined diffraction peak is also observed in the XRD pattern. According to the results of EDS analysis and the literature report of Stoyko, the unknown diffraction peak may be the ternary compound RE 12 Fe 57.5 As 41 [14].…”
Section: Resultsmentioning
confidence: 99%
“…With decreasing temperature, the solubility of As in Fe decreases gradually, and the solubility of As in Fe is less than 5% at room temperature [11,12,13]. Different atomic ratios of cerium (lanthanum), Fe, and As can form the ternary compounds RE 12 Fe 57.5 As 41 (RE=La, Ce) and FeAs at 1173 K [14,15]. The ternary compound La 10 Fe 50 As 40 is formed by the La–As–Fe system at 1223 K [16].…”
Section: Introductionmentioning
confidence: 99%
“…As form the ternary compound RE12Fe57.5As41 (RE=La, Ce) and FeAs at 1173 K [13][14] , whereas the Re-Fe-As ternary system forms La10Fe50As40 15 at 1223 K. In recent years, one of products of RE-Fe-As ternary system named EuFe2As2 [16][17][18][19][20] has attracted significant attention. Xie 21 and Fu 22 investigated the interaction of Nd-Fe-As system at high temperatures and found that the formation of the ternary compound NdFeAs depends on the formation of NdAs and FeAs2.…”
Section: Introductionmentioning
confidence: 99%